Refrigerant Selection for Heat Pumps: The Compressor Makes the Difference. Issue 4 (23rd February 2023) - Neumaier, Lisa; Roskosch, Dennis; Schilling, Johannes; Bauer, Gernot; Gross, Joachim; Bardow, André
Abstract : Increasingly stringent regulations and new applications require selecting improved refrigerants for heat pumps. The selected refrigerants should be environmentally friendly and maximize the performance of the heat pump process. Systematic refrigerant selection methods usually model the compressor with one fixed isentropic efficiency identical for all refrigerants. However, compressor studies indicate that the isentropic efficiency may be highly refrigerant‐dependent. Herein, the need for a refrigerant‐dependent compressor model for refrigerant selection is investigated. For this purpose, a refrigerant‐dependent compressor model is combined with an integrated design of refrigerant and heat pump process. To guarantee a comparable nominal heating power among refrigerants, the compressor design is tailored to the refrigerant by expanding the refrigerant‐dependent compressor model toward compressor sizing. Integrating compressor design into systematic refrigerant selection is enabled by a computationally efficient model implementation. Accounting for refrigerant‐dependent compression substantially changes the resulting refrigerant ranking compared to the widely used assumption of identical isentropic efficiencies for all refrigerants: The best‐performing refrigerant is not even identified among the best ten refrigerants when assuming identical isentropic efficiencies. Consequently, compression is identified as the main driver for differences in refrigerant performance. Therefore, integrating refrigerant‐dependent compressor models is crucial for systematic refrigerant selection. Abstract : Herein, it is shown that the selection of refrigerant requires a compressor model that accounts for the impact of the refrigerant. For this purpose, a refrigerant‐dependent compressor model is combined with an integrated design of refrigerant and heat pump process.